Control of epidemics in the Roman army: 27 B.C. - A.D. 476 - Belfiglio, Valentine J. (International Journal Of Community Medicine And Public Health, 2017)
During the Roman Empire thousands of soldiers were exposed to communicable diseases. The Romans forged a military medical system that surpassed the medical systems of most of their enemies. Under the principles of immediacy and expectancy, the Roman medical staff salvaged and returned to duty many sick and wounded soldiers as rapidly as possible. The selection of and training of healthy legionnaires, hygiene and sanitation and immediate medical care emphasized that the timing of care after diagnosis is as important as the quality of care. The Romans were the first army in history to employ medical corpsmen, field hospitals and triage. The Roman efficacy in combat medicine may be one of the least appreciated aspects of the ability of the Roman army to help create and maintain an empire.